2021
DOI: 10.1039/d1qi00233c
|View full text |Cite
|
Sign up to set email alerts
|

Water-mediated reduction of [Cu(dmp)2(CH3CN)]2+: implications of the structure of a classical complex on its activity as an anticancer drug

Abstract: The interplay between coordination geometry and reactivity in copper complexes has been widely studied for years. For CuII, it is known that the reduction is favored when the geometry is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 76 publications
1
23
0
Order By: Relevance
“…The 1:2:2:1 integration ratio of the hyperfine signals, together with the values of α N = 14.9 G and α β H = 14.89 G, unequivocally prove that the species generated by the BDD substrate is [DMPO–OH] • (Figure b). This indicates the straightforward adduct-formation reaction between • OH and DMPO in eq . Experiments at variable pH (Figure S2) showed that the formation of the [DMPO–OH] • is also observed at more acidic pH values. In contrast, the formation of the [DMPOO] • species was observed at pH 7.…”
Section: Resultsmentioning
confidence: 78%
“…The 1:2:2:1 integration ratio of the hyperfine signals, together with the values of α N = 14.9 G and α β H = 14.89 G, unequivocally prove that the species generated by the BDD substrate is [DMPO–OH] • (Figure b). This indicates the straightforward adduct-formation reaction between • OH and DMPO in eq . Experiments at variable pH (Figure S2) showed that the formation of the [DMPO–OH] • is also observed at more acidic pH values. In contrast, the formation of the [DMPOO] • species was observed at pH 7.…”
Section: Resultsmentioning
confidence: 78%
“…DHR‐123 is a mitochondria‐associated probe which specifically reacts with hydrogen peroxide. Complex 70 , incubated in different concentrations from 0.5 to 2.5 μ M in the cell lines of MG‐63, A549, MCF7 and MDA‐MB‐231 showed a huge increase on the ROS generation in a dose dependent manner from 0.5 to 2.5 μM, while complex 71 was silent in the same experimental condition [127] …”
Section: Copper Complexes Used In Chemotherapeutic Approachmentioning
confidence: 93%
“…Absorption in the UV region corresponds to the π–π* transitions of the phenanthroline ligands (and the pyrene group in the case of complex 3 ), and the absorption band at 450 nm accompanied with a shoulder band at 550 nm is characteristic of the metal-to-ligand charge transfer (MLCT) band of this 2,9-dialkylphenanthroline copper complex family. , This “autoreduction” phenomenon has been already investigated in the case of 6,6′-dialkyl-2,2′-bipyridine ligand . Partial and slow reduction have also been observed for the parent complex Cu II (dmp) 2 without being further investigated. , In this work, the fast reduction of all three complexes, especially in DMF, is undoubtedly triggered by the high redox potential and the higher constraint brought by the bulky substituent to the Cu­(II) geometry. This is especially the case in non-coordinating solvents where the Cu­(II) metal cannot coordinate a fifth ligand to adopt a more favorable geometry.…”
Section: Resultsmentioning
confidence: 97%
“…74 Partial and slow reduction have also been observed for the parent complex Cu II (dmp) 2 without being further investigated. 75,76 In this work, the fast reduction of all three complexes, especially in DMF, is undoubtedly triggered by the high redox potential and the higher constraint brought by the bulky substituent to the Cu(II) geometry. This is especially the case in non-coordinating solvents where the Cu(II) metal cannot coordinate a fifth ligand to adopt a more favorable geometry.…”
Section: ■ Introductionmentioning
confidence: 93%